Good dog, bad cop [large type] - Rosenfelt, David (Rosenfelt, David. K Team novels, 2023)
"Corey's former mentor, Jimmy Dietrich, had his whole identity wrapped up in being a cop. When Jimmy retired three years ago, he had to adjust to life as a civilian. Not long after, two bodies were found on Jimmy's boat, adrift in the ocean. A local woman, Susan Avery, and Jimmy Dietrich. With no evidence, the deaths went unsolved. This didn't stop the whispers: an affair gone wrong... a murder-suicide committed by Jimmy. Corey never believed it. With this case, the K Team has the opportunity to find the real murderer, and clear Jimmy's name"--